Hadith #2877 - Sunan al-Nasa'i - Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Bashr bin Khalid al-'Askary بشر بن خالد العسكري; Imran bin Bakar al-Kula'i عمران بن بكار الكلاعي; Shym al-Madni Mwla biny Zhrh سحيم المدني مولى بني زهرة (Sunan al-Nasa'i)
“The Messenger of Allah came on the fourth day of Dhul-Hijjah having entered Ihram for Hajj. He prayed Subh in Al-Batha and said: ‘Whoever wants to make it Umrah, let him do so.'”
Grade: